Use Of Educational Innovations and Methods in The Development of Students' Biology - Aminjonova Ch.A.; Shodmonova X.S. (Genius Journals, 2022)
The goal of biological education at the present stage is to prepare a biologically and environmentally competent person who must understand the significance of life as the highest value. A modern person, no matter what type of activity he prefers in the future, should be able to build his relations with nature on the basis of respect for man and the environment.
Keywords: Educational Innovations; Training; Biology; Rational Methods